MODALITAS SEBAGAI PERANTI SISTEM APPRAISAL DALAM TEKS IKLAN KULINER KHAS SEMARANG DI MEDIA INTERNET - Nanik Setyawati; Riyadi Santosa; Sumarlam Sumarlam; Dwi Purnanto (Haluan Sastra Budaya, 2021)
Persuasive power in the language of advertising can be reflected in the structure of words, phrases, or clauses in the contents of written or spoken advertisements. Most ad text uses verbal and nonverbal symbols to convey the intent and purpose. The use of language in advertising is adjusted to the needs and to achieve the purpose of the ad. Linguistic research specifically looking at appraisal devices in culinary text advertisements on the internet has an important role in uncovering the ideology of their makers. Through appraisal device studies, especially modalities in ad text on the internet media will be able to know and understand the attitude of advertisers towards the reality that surrounds them, namely their assessment of the advertised goods and the assessment of their environment. This qualitative research refers to Sudaryanto's opinion in providing data and data analysis. Provision of data using the method of referencing and note taking. Data analysis methods and techniques use the method of sharing with basic techniques, namely techniques for direct elements; while the advanced technique uses the technique of fade and dressing techniques. Through a series of analyzes, it was found that there was a use of modality: intentional, epistemic, deontic, and dynamic in the culinary ad text typical of Semarang.